Zinc as an adjunct treatment for reducing case fatality due to clinical severe infection in young infants: study protocol for a randomized controlled trial - Nitya Wadhwa; Sudha Basnet; Uma Chandra Mouli Natchu; Laxman P. Shrestha; Shinjini Bhatnagar; Halvor Sommerfelt; Tor A. Strand; the zinc sepsis study group; Siddarth Ramji; K. C. Aggarwal; Harish Chellani; Anuradha Govil; et al. (BMC, 2017)
Abstract Background An estimated 2.7 of the 5.9 million deaths in children under 5 years of age occur in the neonatal period. Severe infections contribute to almost a quarter of these deaths. Mortality due to severe infections in developing country settings is substantial despite antibiotic therapy. Effective interventions that can be added to standard therapy for severe infections are required to reduce case fatality. Methods/Design This is a double-blind randomized placebo-controlled parallel group superiority trial to investigate the effect of zinc administered orally as an adjunct to standard therapy to infants aged 3 days up to 2 months (59 days) hospitalized with clinical severe infection, that will be undertaken in seven hospitals in Delhi, India and Kathmandu, Nepal. In a 1:1 ratio, we will randomly assign young infants to receive 10 mg of elemental zinc or placebo orally in addition to the standard therapy for a total of 14 days. The primary outcomes hospital case fatality, which is death due to any cause and at any time after enrolment while hospitalized for the illness episode, and extended case fatality, which encompasses the period until 12 weeks after enrolment. Discussion A previous study showed a beneficial effect of zinc in reducing the risk of treatment failure, as well as a non-significant effect on case fatality. This study was not powered to detect an effect on case fatality, which this current study is. If the results are consistent with this earlier trial, we would have provided strong evidence for recommending zinc as an adjunct to standard therapy for clinical severe infection in young infants. Trial registration Universal Trial Number: U1111-1187-6479, Clinical Trials Registry - India: CTRI/2017/02/007966 : Registered on February 27, 2017.